The Effect of Raw Material Costs and Labor Productivity on Production Results (Case Study in the Dungus Tamiang Community) - Raifa Nur Hidayah; Rita Tri Yusnita; Suci Putri Lestari (Journal of Indonesian Management, 2022)
This study aims to determine and analyze the effect of raw material costs and labor productivity on production results. The method used in this study is a quantitative method with multiple linear regression analysis tools and the data used are primary and secondary data. The calculation results show that there is a very strong relationship between the variable costs of raw materials and labor productivity on production results. Based on this research, the cost of raw materials and labor productivity simultaneously have a significant effect on production results. Partial raw material costs have a significant effect on production results. Labor productivity has a significant effect on production results. The results of the calculation show that there is a very strong relationship between the variables of raw material costs and labor productivity on production results.